Nursing Students' Perception of Medical Information Protection in Hospitals - Jeong, Hyeon-Cheol (International journal of e-health and medical communications, 2018)
The purpose of this article is to investigate the perception of medical information protection. The subjects were 281 students from 2 nursing students from September 1, 2015 to October 20, 2015. A total of 28 self - administered questionnaires were used. As a result, the perception of medical information protection behavior was 3.39 ± 0.51. In the fourth grade, the 'privacy protection' category was low (p = .007) and the 'communication' category was high (p = .045). In case of having experience in practice, 'privacy protection' category (p = .010) and ‘medical information management' category (p = .041) were low and 'communication' (p = .021) was high. In the 'communication' category, the perception score was high when the medical information protection law (p = .001) and the nurses' code of ethics (p = .040) were known. When the subject completed 'medical security education' (p = .004), the perception was high. In conclusion, it is necessary for schools and medical institutions to develop nursing education programs for their educational environment and role.